Analysis of Mathematical Models for Gurame Cultivation Systems in Empang Ponds in Tembelang Bekasi Regency - Riri Sadiana; Hengki Rahmanto (Mestro, 2021)
The system of gouramy cultivation in ponds conducted by the community of Tambelang Bekasi Regency is still based on their experiences that develop in an unwritten manner with the application of the Pendederan I, Pendederan II, and Pendederan III systems to anticipate the length of time they need to go from ready to consumption. Pendederan II in addition to the need for optimization on input variables (feed, sente leaves, area maintenance officers) is also a transition period that is vulnerable to predators or predators such as snakes, bats, and cork fish. Techniques and methods for dealing with predators are being developed by these farmers. The analytical approach that examines the system of gouramy cultivation in pond ponds conducted by the Tambelang Bekasi Community becomes a very urgent matter considering that the results of preliminary studies conducted on yields obtained in nursery II only range from 60% to 70% of the entire seedling population distributed . The results of the analysis of mathematical models of carp culture in pond ponds in Tambelang District, Kabasi show the results that mathematical solutions through numerical simulation are strongly influenced by intrinsic rate and emphasis on the number of predators in the form of pool sterilization efforts every three months.